Формализованные показатели для оценки качества радиотехнических систем охраны периметров объектов - Kolesnik, K. V.; Kipenskii, A. V.; Machekhin, Yu. P.; Churyumov, G. I. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
Quality estimation method based on the use of formal parameters, which greatly simplifies the process of creating effective radio systems for perimeter security of distributed objects in the design phase is proposed.